Meta-inflammation in type 2 diabetes mellitus: unveiling the role of aberrant CD4+ T cells and pro-inflammatory cytokine networks - Shaw, Shubham K.; Sengupta, Soumya; Jha, Rohila; Pattanaik, Chandrasekhar; Behera, Harapriya; Barik, Prakash K.; Meher, Dayanidhi; Sarangi, Rajlaxmi; Devadas, Satish (Frontiers in Immunology, 2025)
This study aimed to investigate the causal or casual relation between dysregulated glucose metabolism and meta-inflammation in type 2 diabetes mellitus (T2DM), and more importantly the mediators and cellular sources for this meta-inflammation. We examined whether T2DM meta-inflammation is driven by aberrant, inflamed T-helper cells and if there was a direct link to HbA1c levels. Flow cytometry data revealed TNF-α−secreting effector CD4+ T cells as key contributors to inflammation, while memory T cells secreting GM-CSF and IL-17 escalated and maintained meta-inflammation. Crucially, these cytokines were present even in the “resting CD4+ T cells,” reflecting an aberrant, low-grade, chronically activated, and inflamed immune system. Significantly, higher antibody isotype levels further substantiated these findings as proof of concept for sustained and inflamed APC-T cell-B cell nexus. while reduced IL-10 levels reflected a shift towards pro-inflammatory bias. Functional assays, phospho-protein expression, ex-vivo inhibitor studies, and confocal microscopy confirmed that basal meta-inflammation in T2DM is exclusively mediated by multiple T-helper cell phenotypes via the TNF-α/STAT-3-signaling axis. Plasma cytokine and antibody isotyping were profiled using multiplex immunoassays from undiluted plasma. Taken together, these findings suggest that unchecked cytokine secretion, inflamed T-helper subsets, unwarranted antibody isotypes, and so forth, may contribute to organ damage by further amplifying innate and adaptive immune responses. Monitoring inflammatory cytokines, antibody isotypes, and T-helper cell subsets could significantly mitigate organ damage in T2DM, offering a more comprehensive approach to disease management. Thus, this study highlights the importance of not only achieving metabolic control during T2DM treatment but also monitoring and regulating immune homeostasis.